Impulse Control Disorders in Parkinson’s Disease: Crossroads between Neurology, Psychiatry and Neuroscience - Paulo Bugalho; Albino J. Oliveira-Maia (Behavioural Neurology)
Non-motor symptoms contribute significantly to Parkinson’s disease (PD) related disability. Impulse control disorders (ICDs) have been recently added to the behavioural spectrum of PD-related non-motor symptoms. Such behaviours are characterized by an inappropriate drive to conduct repetitive behaviours that are usually socially inadequate or result in harmful consequences. Parkinson disease impulse control disorders (PD-ICDs) have raised significant interest in the scientific and medical community, not only because of their incapacitating nature, but also because they may represent a valid model of ICDs beyond PD and a means to study the physiology of drive, impulse control and compulsive actions in the normal brain. In this review, we discuss some unresolved issues regarding PD-ICDs, including the association with psychiatric co-morbidities such as obsessive-compulsive disorder and with dopamine related side effects, such as hallucinations and dyskinesias; the relationship with executive cognitive dysfunction; and the neural underpinnings of ICDs in PD. We also discuss the contribution of neuroscience studies based on animal-models towards a mechanistic explanation of the development of PD-ICDs, specifically regarding corticostriatal control of goal directed and habitual actions.